2007
DOI: 10.1029/2006jd008207
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous oxidation of sulfur dioxide by ozone on the surface of sodium chloride and its mixtures with other components

Abstract: [1] The heterogeneous oxidation of SO 2 by O 3 on NaCl particles has been studied using diffuse reflectance infrared Fourier transform spectroscopy. The formation of sulfite and sulfate on the surface was identified, and the roles of O 3 and water in the oxidation processes were determined. The results showed that in the presence of O 3 , SO 2 could be oxidized to sulfate on the surface of NaCl particles. The reaction is first order in O 3 and zero order in SO 2 . The initial reactive uptake coefficient for SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…With the reaction on -Al 2 O 3 , the presence of NO 2 improved the oxidation of SO 2 [17]. Li et al [11] studied the heterogeneous oxidation of SO 2 by ozone on the surface of sodium chloride and mixtures with other components using in situ DRIFTS and proposed a three-stage mechanism: (1) O 3 was adsorbed on the NaCl surface, which resulted in an alkalescent surface; (2) the adsorption of SO 2 was then followed by (3) O 3 oxidation. The adsorption of O 3 on the NaCl surface was the rate-determining step.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…With the reaction on -Al 2 O 3 , the presence of NO 2 improved the oxidation of SO 2 [17]. Li et al [11] studied the heterogeneous oxidation of SO 2 by ozone on the surface of sodium chloride and mixtures with other components using in situ DRIFTS and proposed a three-stage mechanism: (1) O 3 was adsorbed on the NaCl surface, which resulted in an alkalescent surface; (2) the adsorption of SO 2 was then followed by (3) O 3 oxidation. The adsorption of O 3 on the NaCl surface was the rate-determining step.…”
Section: Introductionmentioning
confidence: 98%
“…Studies since the 1970s have demonstrated that the uptake of SO 2 on particles leads to sulfite and sulfate formation [9]. The reaction mechanism and kinetics are related to the physical and chemical characteristics of the particles, such as surface active sites, acidity, and surface area [10][11][12][13]. Studies have focused on mineral particles and sea salts.…”
Section: Introductionmentioning
confidence: 99%
“…Such transformations in aerosol particles affect both the environment and human health Tang et al, 2006;Wei et al, 2009). In the context of their close relationship to aerosol surface area, morphology, surface chemical composition, structure and other surface characteristics (Zhu et al, 2010;Lazzeri et al, 2003;Xu, 2006;Li et al, 2007;Li et al, 2010;Wu et al, 2009;Lu et al, 2013;Bluhm and Siegmann, 2009;Sobanska et al, 2014), study of the surface physicochemical characteristics of aerosol particles has become an important aspect of aerosol particle research.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the calculated production of sulfate mentioned above includes only the production in the gas phase and in the aqueous bulk of droplets. The heterogeneous chemistry on the surface of droplets and aerosols is potentially important (Li et al, 2006(Li et al, , 2007Ammann and Pöschl, 2007;Pöschl et al, 2007;Chen et al, 2008), but it is not taken into account in the above estimation. Jayne et al (1990) observed that the uptake of SO 2 into water droplets was faster than predicted on the basis of the known kinetics in bulk solution, and they suggested that a surface complex was formed between SO 2 and H 2 O at the interface.…”
Section: Formation Of Hydroperoxides By Ozonolysismentioning
confidence: 99%